Transformation in governance towards resilient food systems - Bers, Caroline van; Pahl-Wostl, Claudia; Eakin, Hallie; Ericksen, Polly J.; Lenaerts, Lutgart; Förch, Wiebke; Korhonen-Kurki, Kaisa; Methner, Nadine; Jones, Lindsey; Vasileiou, Ioannis; Eriksen, Siri H. (2016)
The dynamics of systemic societal transformations are not well understood, and the extent to which such transformations can be governed is contested. This research paper is the result of a joint effort among a small group of researchers to identify pathways for transformation towards sustainable food systems, which are resilient towards shocks and towards climate change in particular. Using empirical studies, both transformations in governance systems and governance of transformations were investigated. These cases served as a preliminary analysis to identify some of the trends and patterns that warrant further investigation. Not surprisingly, transformational change in food systems is often triggered by a shock to the system, or by increasing pressure to that system. But that alone is not enough to bring about a transformation. A number of preconditions and conditions need to be present including sufficient ‘wealth’ or economic and social capital in the system with resources that can be mobilized, and sufficient flexibility in the institutional context to allow innovation to emerge and gain strength. A particular area of interest that appears to stimulate transformations is collective action, which often involves collaboration across geographical scales and interest groups. The outcomes of transformations are complex and typically multifaceted, and can take years to emerge. However, broadly speaking, the cases explored demonstrate that governance is central to food system transformation both in terms of pre-conditions and provoking processes as well as in the outcomes of the transformation itself. Food system transformations in general appear to entail fundamental shifts in social relations and institutions – in other words, the governance of the food system.